2021
DOI: 10.1111/aje.12878
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal sharing and partitioning of scent‐marking sites by cheetahs and leopards in north‐central Namibia

Abstract: Scent‐marking sites may facilitate interspecific information gathering and could help to minimise the risk of encounter with interspecific competitors. Recent evidence from South Africa shows that cheetahs avoid dominant predators at scent‐marking sites, which may delay or inhibit intraspecific communication in cheetahs. However, little is known on whether this pattern of avoidance occurs elsewhere in the cheetah's range. We analysed a 9‐year camera trap data set from north‐central Namibia to explore interspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Cheetahs can be particularly active during lunar cycles with increased moonlight, a strategy thought to increase nocturnal hunting efficiency (Broekhuis et al, 2014;Searle et al, 2021). Our findings on cheetah movements show a predominance of long movements during the crepuscular period, which might place them at risk of encountering a dominant competitor, the leopard (Verschueren et al, 2021).…”
Section: Factors Associated With Movementsmentioning
confidence: 67%
See 1 more Smart Citation
“…Cheetahs can be particularly active during lunar cycles with increased moonlight, a strategy thought to increase nocturnal hunting efficiency (Broekhuis et al, 2014;Searle et al, 2021). Our findings on cheetah movements show a predominance of long movements during the crepuscular period, which might place them at risk of encountering a dominant competitor, the leopard (Verschueren et al, 2021).…”
Section: Factors Associated With Movementsmentioning
confidence: 67%
“…Cheetahs, particularly males use marking trees repeatedly for territorial and reproductive advertising (Marker-Kraus and Kraus, 1997), whereas in leopards both sexes often scent mark (Cornhill and Kerley, 2020). Cheetahs and leopards often choose the same marking trees but exhibit temporal segregation to avoid conflict (Rafiq et al, 2020;Verschueren et al, 2021).…”
Section: Factors Associated With Movementsmentioning
confidence: 99%
“…Our temporal segregation hypothesis was not statistically supported, yet we detected a possible slight shift in prey activity peaks from morning (~6:00) to evening (~18:00) with cheetah presence. The activity patterns of ungulates in our system could be partially related to risk avoidance tactics, as cheetah activity tends to peak in the early morning (~6:00) in the broader region [ 64 ]. Studies evaluating risk avoidance behaviour by ungulates have observed stronger adaptive responses of prey species to ambush hunters (i.e., leopard) compared to cursorial hunters (i.e., cheetahs) [ 5 , 40 , 46 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Savannas, in particular, profit from those apex predators because the trophic impact exacted by carnivores strongly shapes and maintains an ecosystem’s balance 29 31 . In Sub-Saharan Africa, cheetahs and leopards inhabit similar open habitats and often share a sympatric distribution 32 , 33 . Their coexistence is a result of niche partitioning.…”
Section: Introductionmentioning
confidence: 99%